Improving occupational health and safety data integration using building information modelling - an initial literature review - Tender, M. (2022)
The main objective of this paper is to address the technical-scientific gap identified in the literature by presenting an overview of the existing coverage of the use of BIM (Building Information Modelling) for Occupational Health and Safety (OHS) management. The Scopus and Web of Science research literature databases were selected as the most suitable for the literature review. Appropriate keywords were identified and a search in each of the databases was performed, resulting in a satisfactory number of papers. Priority was given to papers from sources with peer reviewand a high impact factor. The main findings reveal the areas whereBIM related digital technologies are being applied to improve H&S management outcomes. This work fills a gap in the existing literature and provides a platform for the development of improved safety management systems resulting in more efficient H&S processes and increased productivity whichwill provide a stronger link between production and safety. The number of research studies will increase as people realize the importance of OHS in the digital data environment and recognize the advantages of using BIM and related technologies. Future research should explore in more detail some of the areas identified and establish the benefits of using digital technologies to improve OHS outcomes. New emerging technologies such as Virtual Reality, Augmented Reality, Internet of Things, Big Data, Artificial Intelligence and their integration with BIM will certainly become essential areas of research in the future.